2022
DOI: 10.1136/bmjoq-2021-001807
|View full text |Cite
|
Sign up to set email alerts
|

Defining case management success: a qualitative study of case manager perspectives from a large-scale health and social needs support program

Abstract: ObjectiveHealth systems are expanding efforts to address health and social risks, although the heterogeneity of early evidence indicates need for more nuanced exploration of how such programs work and how to holistically assess program success. This qualitative study aims to identify characteristics of success in a large-scale, health and social needs case management program from the perspective of interdisciplinary case managers.SettingCase management program for high-risk, complex patients run by an integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Trusting relationships between patient and case manager have been found to help patients feel more secure and empowered to make decisions and take actions to support their health [ 16 , 24 ]. Patient trust may also be an important indicator of success in case management programs [ 24 ]. Additionally, we found that a positive relationship with a case manager may help to mitigate the impacts of mental health challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Trusting relationships between patient and case manager have been found to help patients feel more secure and empowered to make decisions and take actions to support their health [ 16 , 24 ]. Patient trust may also be an important indicator of success in case management programs [ 24 ]. Additionally, we found that a positive relationship with a case manager may help to mitigate the impacts of mental health challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research validates this fact. Current literature by Knox et al (2022) firmly acknowledges case management's interdisciplinary expertise, especially in addressing health-related social needs and other social determinants of health. However, incorporation of interprofessional perspectives within existing case management models continues to yield challenges.…”
Section: Interprofessional Expertisementioning
confidence: 99%
“…16 Therapeutic alliance itself appears to affect treatment and outcomes, for example, stronger therapeutic alliance is related to higher levels of clinician optimism about patient recovery, a greater sense of personal growth, 17 clinician flexibility, and opportunities to observe and respond to changes in patients' mindsets. 18 Other studies explored the clinician's experience of treatment, for example their preferences or how it affects them personally. One study found that a recovery oriented or strengths-based approach had positive effects on professional and personal satisfaction for providers in community based rehabilitation settings.…”
Section: Clinician Experience Of the Process Of Rehabilitationmentioning
confidence: 99%
“… 16 Therapeutic alliance itself appears to affect treatment and outcomes, for example, stronger therapeutic alliance is related to higher levels of clinician optimism about patient recovery, a greater sense of personal growth, 17 clinician flexibility, and opportunities to observe and respond to changes in patients’ mindsets. 18 …”
Section: Introductionmentioning
confidence: 99%